Design of Compandor Based on Approximate the First-Degree Spline Function - Velimirovic, L.; Peric, Z.; Stankovic, M.; Nikolic, J. (Elektronika ir Elektrotechnika, 2013)
In this paper, the approximation of the optimal compressor function using spline function of the first-degree is done. For the companding quantizer designed on the basis of the approximative spline function of the first-degree, the support region is numerically optimized to provide the minimum of the total distortion for the last segment. It is shown that the companding quantizer with the optimized support region threshold provides the signal to quantization noise ratio that is very close to the one of the optimal companding quantizer having an equal number of levels. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5911